A Derivatographic Method for Determining the Kinetic Parameters of Thermal Degradation of Developed Ion-Exchange Materials - Tadjihodjaev Zakirkhodja Abdusattarovich; Sodikova Munira Rustambekovna (Genius Journals, 2024)
The article describes the application of the derivatography method for the developed ionexchange materials in order to determine the kinetic parameters of the thermal degradation process. The methods of calculation of the main kinetic parameters – the activation energy and the order of the thermal degradation reaction of ion-exchange materials according to thermogravimetric analysis are presented. It is revealed that the destructive processes of ion-exchange materials belong to the reactions of the first order. It is determined that the developed ion-exchange materials are at the same level in terms of thermal stability and the nature of their decomposition can be explained by the destruction of the corresponding bonds.
Keywords: thermal stability; thermogravimetric analysis